Pharmaco Penile Duplex Ultrasonography in the Evaluation of Erectile Dysfunction - Phani Chakravarty Mutnuru (Journal of Clinical and Diagnostic Research, 2017)
Introduction: The National Institute of Health defined ‘erectile dysfunction’ as the persistent inability to achieve and/or to maintain an erection for a satisfactory sexual performance. In last few years, the concept of erectile dysfunction has evolved from that of a disorder referred to as ‘impotence’ which used to be considered predominantly psychogenic to that of ‘Erectile Dysfunction’ (ED), a well understood physiologic result of multiple risk factors, both psychological and organic. The most common cause of organic erectile dysfunction is vasculogenic causes. Doppler evaluation of cavernosal arteries after intracavernosal injection of Papaverine is particularly useful in the evaluation of vasculogenic causes. Aim: To define the role of intracavernosal injection of Papaverine in the evaluation of vasculogenic causes of erectile dysfunction that includes arterial insufficiency and veno occlusive nature. Materials and Methods: Pharmaco Penile Duplex Ultrasonography (PPDU) was done using a linear broadband phased array transducer (7–12 MHz) on a E-Saote MyLab 60 ultrasound colour Doppler system on 73 patients over a period of three years. Informed consent was taken from all patients. Visual grading score for erection, Cavernosal Artery Diameter (CAD), PSV (Peak Systolic Velocity), EDV (End Diastolic Velocity), RI (Resistive Index), AT (Acceleration Time) and dorsal vein changes were obtained in all patients following intracavernosal injection of Papaverine. Results: Visual grading for erectile response was E0 in one patient, E1 in 11 patients, E2 in 9 patients, E3 in 7 patients, E4 in 4 patients and E5 in 41 patients. Eighteen patients were diagnosed as having arterial insufficiency, three patients were diagnosed as having venous insufficiency and two patients showed indeterminate results. Conclusion: In our study, Papaverine induced PPDU proved to be highly accurate and excellent method for assessing patients with erectile dysfunction.